The Influences of Job Characteristics, Emotional Quotient, and Spiritual Quotient on Job Satisfaction and Nurses Performance At Islamic Hospital in Gresik - Mauladi, Kemal Farouq (Archives of Business Research, 2019)
The research purpose was to analyze the influences of job characteristics, emotional quotient and spiritual quotient on job satisfaction and nurse performance at Islamic Hospitals in Gresik. The research approach using quantitative Research, population of this study is nurses in Three Islamic Hospitals in Gresik, with a total sample of 240 nurses. The data analysis technique uses Structural Equation Modeling (SEM). The results of this study indicate job characteristics influences performance, emotional quotient also influences job satisfaction and performance, while the spiritual quotient only influences job satisfaction, and effects of job characteristics on job satisfaction and spiritual quotient on performance are not significant. Finally, job satisfaction also influences performance